Control Methodology Competitiveness of the Processing Industry in the Republic of Belarus - N. N. Voroshilina (Управленческое консультирование)
The article is devoted to the problem of ensuring the competitiveness of enterprises of the manufacturing industry in the Republic of Belarus, which is one of the most important tasks of economic policy, which largely determines its national security. The article discusses three main approaches that provide the most comprehensive analysis of competitiveness.The aim of the study is to reveal the essence of the main categories: competitiveness management, the subject of competitiveness management, the goals of competitiveness management, the form of technologization of competitiveness management, methods for implementing competitiveness management functions; existing approaches to the organization of management of the competitiveness of manufacturing enterprises of the Republic of Belarus.A content analysis of the works of domestic and foreign scientists devoted to the issue of competitiveness, the Law of the Republic of Belarus on Counteracting Monopolistic Activities and the Development of Competition, the statistical collection “Regions of the Republic of Belarus. Socio-economic indicators” of the National Statistical Committee of the Republic of Belarus.Methods of comparative, logical and economic-statistical analysis were used. The paper analyzes the existing approaches to the technology of enterprise competitiveness management.It is concluded that the dependence of the value of the enterprise’s competitive advantages on the quantitative and qualitative characteristics of the aggregate of production resources requires the inclusion of the stage of assessing production resources in the competitiveness management algorithm.